THE INFLUENCE OF THE IMPLEMENTATION OF THE SAM'IYAH SYAFAWIYAH METHOD AND POWER POINT ON ARABIC LEARNING OUTCOMES OF CLASS X ACCOUNTING AT SMK MUHAMMADIYAH 1 GENTENG - Taslim Taslim (Program Pasca Sarjana, Universias PGRI Argopuro Jember, 2022)
This study aims to know the influence of the application of the Sam'iyah Syafawiyah Method and Power Point-based Learning on Arabic Learning Outcomes. The subjects of this study were students of Class X Accounting for Odd Semester students at SMK Muhammadiyah 1 Genteng 2020-2021 Academc Year. This research used a quantitative-causality approach, which is an approach that examines causal relationships. Determination of the research area using purposive sampling area. The population was 75 students, while the sample was 50 students. The data collection techniques were the questionnaire method, observation, documentary and test methods. While the method of analysis of this research used multiple linear regression analysis and Anova test with SPSS 23. This research resulted in three things: (1) There was an influence of the Sam'iyah Syafawiyah method on Arabic Language Learning Outcomes of Class X Accounting; (2) there was an influence of Power Point-Based Learning on Arabic Learning Outcomes of Class X Accounting; (3) there was a significant influence of the implementation of both Sam'iyah Syafawiyah Method and Power Point-Based Learning on the learning outcomes of Class X Accounting.